Primary retroperitoneal liposarcoma with extensive ossification: A case report. Issue 13 (March 2019) - Xin, Qi; Liu, Xingkai; Yu, Xiaoyuan; Ye, Junfeng; Peng, Xiaofan; Zhou, Mingming; Zhang, Ping
Abstract: Rationale: Primary retroperitoneal liposarcoma, which originates from mesenchymal tissues, can rarely present with extensive ossification. Patient concerns: A 41-year-old male patient presented with a chief complaint of discomfort around the waist for 2 months. Diagnoses: Computerized tomography (CT) and magnetic resonance imaging suggested a lesion of approximately 5.6 × 5.1 × 8.7 cm in front of the psoas major muscle, which was considered to be a mesenchymal or neurogenic tumor. Interventions: The hard mass was removed by laparotomy, and the pathological investigation revealed that this was an atypical lipomatous tumor/well-differentiated liposarcoma, with extensive ossification. Outcomes: The patient was discharged from the hospital after surgery. There was no sign of reoccurrence after 1 year of follow-up. Lessons: Retroperitoneal liposarcomas with extensive ossification are rare tumors that can present with nonspecific symptoms, and are difficult to diagnose. CT is the most common imaging technique, and surgical resection has been considered to be the most effective treatment. This rare case can be challenging for diagnosis and treatment.